Hidden in Plain Sight: Detecting Invasive Species When They Are Morphologically Similar to Native Species - Fisher, Samuel; Fisher, Robert N.; Pauly, Gregory B. (Frontiers in Conservation Science, 2022)
Early detection and rapid response (EDRR)is necessary to help mitigate and control invasive species outbreaks when they start but it is dependent on accurate identification of invasive species. We looked at a novel outbreak in San Diego County of the Sonoran Spotted Whiptail (Aspidoscelis sonorae), an invasive whiptail lizard within California in order to confirm their spread as well as quantify how to better detect and manage this invasive species. We found that they have spread rapidly since they were first detected, and that they went unnoticed for years due to their similarity to native whiptails. Additionally, we overview key diagnostic features to help identify this species from native California whiptails. We also review how to better utilize widely available community science tools to rapidly assess a novel invasive species outbreak. Using our experience we outline suggestions to help manage ways to deal with cryptic invasive species.